Conjugation Of Bioactive Groups To Poly(Lactic Acid) Microspheres For Drug Delivery Systems - Sabee, Mohd Meer Saddiq Mohd (2020)
The development of poly(lactic) acid (PLA) microspheres through the emulsion and solvent evaporation (ESE) method is promising for drug delivery systems (DDS) applications owing to the biocompatibility, biodegradability, non-toxic and excellent mechanical PLA properties. However, hydrophobicity of PLA may result in low cells affinity which can elicit an inflammatory response when administered in vivo. Therefore, in this research, surface functionalization via sodium hydroxide (NaOH) hydrolysis has been conducted to introduce hydrophilic functional groups on the PLA microspheres. Further surface engineered by conjugation with the basic fibroblast (bFGF) and epidermal (EGF) growth factors (GFs) were performed in order to improve its signaling interaction with cells specifically osteoblasts. Whereas, the capability of PLA as a drug carrier was compared between gentamicin and dexamethasone in terms of drug encapsulation efficiency, loading and release profile prior to antimicrobial assessments via Kirby-Bauer agar well diffusion and minimum inhibitory concentration (MIC) on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) strains. It was observed that gentamicin encapsulated at 0.375% were having good encapsulation efficiency (42.3%), loading (26.5×10-3%) and release profile (R2 = 0.9944) of Higuchi model. The highest zone of inhibition for bacterial strains was also observed at 0.375% gentamicin encapsulated PLA microspheres in parallel with the MIC values assessment (0.002 mg/mL). The PLA microspheres modifications done enhanced the cellular homing, migration and differentiation which contribute to a successful drug delivery process. All the modifications performed resulted in increasing osteoblasts proliferation with the highest percentage of cells viability was observed at gentamicin EGF conjugated PLA microspheres on day 5. While, all modifications on PLA microspheres enhanced the migration of the osteoblasts as wound closure was 100% after three days of the cells seeding indicated enhanced in wound healing process. Increase in hydrophilicity of the surface of PLA microspheres offers favorable surface for osteoblasts attachment which was reflected by positive 4’,6-diamidino-2-phenylindole (DAPI) staining of the cells’ nuclei. Other than that, the modifications on the PLA microspheres were able to enhance the capability of the PLA in facilitating the differentiation process of mesenchymal stem cells (MSCs) into osteogenic lineage since only positive stain was observed on the modified PLA microspheres in which the highest intensity occurred by the presence of GFs. These results indicated that the functionalization and conjugation of PLA microspheres with GFs improved the hydrophilicity of the PLA with non-toxic properties. The conjugated PLA microspheres has potential to be used as drug delivery vehicle as evidenced it can enhance the cells adherence, attachment, proliferation and differentiation with prolonged and sustained drug release profile.